2020
DOI: 10.1016/j.meegid.2020.104498
|View full text |Cite
|
Sign up to set email alerts
|

Functional prediction and comparative population analysis of variants in genes for proteases and innate immunity related to SARS-CoV-2 infection

Abstract: New coronavirus SARS-CoV-2 is capable to infect humans and cause a novel disease COVID-19. Aiming to understand a host genetic component of COVID-19, we focused on variants in genes encoding proteases and genes involved in innate immunity that could be important for susceptibility and resistance to SARS-CoV-2 infection. Analysis of sequence data of coding regions of FURIN, PLG, PRSS1, TMPRSS11a, MBL2 and OAS1 genes in 143 unrelated individuals from Serbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
21
0
4
Order By: Relevance
“…Therefore, the correlation between HLA variants and COVID-19 needs to be further studied to pinpoint the effect of genetic factors. In relation, a study of sequence analysis has identified 22 variants in the coding regions of some proteases (FURIN, PLG, PRSS1, TMPRSS11a) and innate immune-related genes (MBL2 and OAS1) in a Serbian population [55]. Using in silico analyses, 10 of these variants were predicted to be proteinaltering variants, possibly affecting the protein's function.…”
Section: Immune System Related Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the correlation between HLA variants and COVID-19 needs to be further studied to pinpoint the effect of genetic factors. In relation, a study of sequence analysis has identified 22 variants in the coding regions of some proteases (FURIN, PLG, PRSS1, TMPRSS11a) and innate immune-related genes (MBL2 and OAS1) in a Serbian population [55]. Using in silico analyses, 10 of these variants were predicted to be proteinaltering variants, possibly affecting the protein's function.…”
Section: Immune System Related Genesmentioning
confidence: 99%
“…On the other hand, the mutations in innate immune-related genes are hypothesized to be disadvantageous to the host, allowing the virus to escape the immune response. These variants include p.Gly146Ser in FURIN; p.Arg261His and p.Ala494Val in PLG; p.Asn54Lys in PRSS1; p.Arg52Cys, p.Gly54Asp and p.Gly57Glu in MBL2; p.Arg47Gln, p.Ile99Val and p.Arg130His in OAS1 [55]. Additional population genetics studies have shown that seven variants in PLG, TMPRSS11a, MBL2 and OAS1 genes experienced genetic divergence (i.e., different allelic frequencies) among different populations worldwide [55].…”
Section: Immune System Related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such upregulated genes included 2'-5'-oligoadenylate synthetase 1 (OAS1), an interferon-responsive gene [48][49][50] , interferon regulatory factor 2 (IRF2), interferon-induced transmembrane protein 2 (IFITM2), secretory leukocyte peptidase inhibitor (SLP1), max dimerization protein 1 (MXD1), tissue inhibitor of metalloproteinase-1 (TIMP1), PH domain-containing adaptor Bam32/DAPP1, and T helper type 1 (Th1)/monocyte-associated chemokine CCL2, which have been shown to also participate in SARS-CoV-2-AEC2 signaling in lung cells 51 . In fact, upregulation of OAS1 and IFITM2 has been recently noticed as a common feature in patients infected with SARS-CoV-2 41 , and certain variants of OAS1 have been predicted to influence SARS-CoV-2 infection 52 . These observations suggest that the noticed reduced expression of the vitamin D pathway in lung cells of patients infected with SARS-CoV-2 could be associated with both down-and upregulation of cellular genes because vitamin D is known to regulate gene expression both positively and negatively.…”
Section: Enrichment Analysis Of 43 Vitamin D-modulated Genes In Samplmentioning
confidence: 99%
“…Indeed, four genetic variants identified in certain protease genes that alter the structure and function of the encoded protease proteins, which consequently cleave SARS-CoV-2 protein to facilitate viral cell entry, could be protective against and decrease the severity of COVID-19 infection. 18 In conclusion, SNPs in ACE2, TMPRSS2, cytokines, TLR-7, androgen receptor and protease genes could have a significant impact on incidence and severity of COVID-19. Performing genetic analysis in patients with COVID-19 to detect these variants could help in risk stratification of patients to plan their management accordingly.…”
mentioning
confidence: 91%